CDNA cloning, expression and bioinformatical analysis of Tssk genes in tree shrews. (June 2021) - Li, Xue; Li, Yuanji; Song, Wenfei; Xie, Daohao; Zhu, Fangfang; Yang, Minghua; Li, Yahui
Highlights: The full-length cDNA of five members of the Tssk family in tree shrews have been cloned. The phylogenetic tree of Tssk genes indicates that tree shrews are closely related to primate animals. Five Tssk recombinant proteins of tree shrews have been produced via genetic engineering. Tssk genes are specifically expressed in the testis/sperm of tree shrews though other tissues express limited mRNA. Bioinformatical analysis reveals characteristics of biochemistry, structure and function of Tssk proteins in tree shrews. Abstract: Tree shrews are more closely related to primate animals than rodents in many aspects. In addition, they also possess several advantageous characteristics including small body size, high brain-to-body mass ratio, low cost of feeding and maintenance, short reproductive cycle and life span, which make them promising novel laboratory animals to replace more precious larger primate animals. T estis-s pecific s erine/threonine k inase (Tssk) plays important roles in spermatogenesis and/or the regulation of sperm function. However, studies on Tssk in tree shrews have not been reported yet. In the present study, the full-length sequences of five members of the Tssk family in tree shrews were cloned and their CDS region sequences were analyzed by basic bioinformatics. The phylogenetic tree and prokaryotic protein expression system of Tssk gene of tree shrews were constructed. The mRNA expressions of Tssk genes in 11 tissues/organs from tree shrews were studied. The results showed that: 1. the length of the CDS region of tree shrew Tssk gene for Tssk1B, Tssk2, Tssk3 (variant X1 / X2), Tssk4 (variant X1 / X2) and Tssk6 is 1080bp, 1077bp, 867 / 807bp, 1014 / 984bp, 822bp, respectively, encoding 359, 358, 288/268, 337/327 and 273 amino acids, respectively; the cloned sequences of Tssk genes have been submitted to GenBank with the following accession numbers: KX091161( Tssk1B ), KX091162( Tssk2 ), KX091163( Tssk3 variant X1)/KX091164( Tssk3 variant X2), KX091165( Tssk4 variant X1)/KX091166( Tssk4 variant X2), KX091160( Tssk6 ). 2. All tree shrew Tssk proteins distribute in cytoplasm, indicating that they are hydrophilic and non-secretory proteins, with multiple phosphorylation sites of serine and/or threonine. In addition, they are all mixed proteins with similar tertiary structures sharing a highly conserved functional domain of S_TKc (Serine/Threonine protein kinases, catalytic domain). 3.The molecular phylogenetic tree of five Tssk genes in tree shrews indicates that they are neither rodent nor primate animal, but are closely related to primate animals. 4. Five members of the Tssk recombinant proteins in tree shrews were successfully obtained using the constructed prokaryotic protein expression system. 5. Five Tssk genes are specifically expressed in the testis and/or sperm of tree shrews. Additionally, small amount of Tssk1B was expressed in several tissues other than testis and sperm. Limited mRNA levels of Tssk2 and Tssk4 were expressed in the brain, while mRNA of Tssk3 or Tssk6 could only be detected in the testis and sperm. This study will provide fundamental data on reproductive biology of tree shrews, which paves a way for further studying Tssk's biological function in this novel model animal.